Blue lasing and strong coupling in ZnSe monolithic microcavities. Issue 9 (7th June 2013) - Sebald, K.; Seyfried, M.; Klembt, S.; Kruse, C.; Aschenbrenner, T.; Hommel, D.; Bley, S.; Rosenauer, A.; Gutowski, J.; Ulrich, Sven M.; Jetter, Michael; Michler, Peter
Abstract Microcavity structures which consist of a cavity formed by two distributed Bragg reflectors can be used to study light‐matter interaction in the weak and strong coupling regime. In this contribution microcavities with one or three ZnSe quantum wells embedded into the cavity are presented. In contrast to the sample with the single quantum well, strong light‐matter coupling can be observed for that one with three quantum wells. The sample possesses an energy splitting of about 19meV between the upper and lower polariton branch observed by reflectivity measurements. In addition, the transition from strong to weak coupling and the starting of the photonic lasing is demonstrated by excitation density dependent measurements. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)